ANALISIS KEPEMIMPINAN MANAJERIAL KEPALA SEKOLAH DALAM MEWUJUDKAN SEKOLAH UNGGUL DI MASA PANDEMI - Yantoro Yantoro; Muhammad sholeh (Jurnal Muara Pendidikan, 2021)
This research is a qualitative research that aims to describe a superior school in a pandemic (an analysis study of the principal's leadership in the development of learning quality). The type of research is phenomenological research. This research was conducted at SD Negeri 47/IV Jambi City, Jambi Province. The time of the study was carried out in the odd semester of 2021/2022. The data taken from this research are primary data and secondary data. Primary data is data obtained from the main source, namely research informants (principals and classroom teachers. Based on the results of observations, interviews, and documentation that have been collected by researchers, it can be explained that the principal of SD Negeri 47/IV Jambi City through his managerial leadership in planning, organizing, implementing, and supervising schools to develop the quality of managerial learning, making strategic plans for school development, where overall planning is related to directing teachers to complete learning administration, activating school Teacher Working Group (TWG) activities, habituation of activities literacy before learning begins.